Study of Intrathecal Clonidine to Magnesium Sulfate as Adjuvants to Hyperbaric Bupivacaine in Subarachnoid Block in Tertiary Care Centre: Editor's Note: This article has been retracted as of January 2026 as it is out of scope (Indian Journal of Public Health Research & Development, 2023)
AbstractBackground: Spinal anaesthesia is the most preferred regional anaesthesia technique as it is easy to perform,economical and produces rapid onset of anaesthesia and complete muscle relaxation. The aim of intrathecal localanaesthetic is to provide adequate sensory and motor block necessary for all infra umbilical surgeries.Aims and Objectives: The aim of the study is to compare the Onset and Duration of Sensory Block; Onset andDuration of Motor Block and other factors in two groups i.e., Hyperbaric Bupivacaine 0.5% with Clonidine 30μg&Hyperbaric Bupivacaine 0.5% with Magnesium sulphate 50 mg when given intrathecally.Materials and Methods: A Comparative three group randomized clinical study with 90 patients with 30 patientsin Group C (Clonidine), 30 patients in Group M (Magnesium) and 30 patients in Group N (Normal saline) to studythe onset of motor and sensory block, changes in hemodynamics and side effects.Results: Our study has demonstrated that Intrathecal clonidine (30 mcg) prolonged post-operative analgesia alongwith earlier onset and prolonged duration of sensory and motor blockade compared to both magnesium (50 mg)and control.Intrathecal magnesium (50 mg) also increased the analgesic duration compared to control but it wasassociated with delayed onset of both sensory and motor blockade compared to both clonidine and control.Conclusion: Clonidine can be a good alternative adjuvant with 0.5% hyperbaric bupivacaine when comparedto others like fentanyl, magnesium, midazolam, ketamine etc. as it provides early onset of sensory and motorblockade and also prolonged duration of post-operative analgesia.
Keywords: Spinal Anesthesia, Bupivacaine, Adjuvants, Clonidine, Magnesium Sulphate.